Pengembangan Potensi Wisata dan Kesesuaian Lahan Wisata terhadap Resiko Tsunami di Kawasan Teluk Pacitan - Rashifah, Nadiyah; Makalew, Afra Donatha Nimia; Zain, Alinda Fitriany Malik (http://arl-faperta.ipb.ac.id/, 2024)
The southern coastal region of Pacitan Regency, particularly in six districts, namely Ngadirejo, Sudimoro, Kebonagung, Donorojo, Pringkuku, and Pacitan District, is classified as a high-risk tsunami red zone. Based on the research findings, the Pacitan Bay area consists of two villages, namely Sidoarjo Village and Ploso Village in Pacitan Distict. Sidoarjo Village covers an area of 8.36 km², while Ploso Village covers 3.66 km², making the total area 12.02 km² or 1202 hectares. The analysis of land suitability for tourism in relation to tsunami risk aims to assess the level of compatibility of a tourist area located in a tsunami-prone region. The environmental vulnerability parameters include elevation, land slope, coastal morphology, land use, distance from the coastline, and distance from rivers. Additionally, bathymetric data and tsunami run-up based on historical tsunami events in the southern coastal areas of Java Island are utilized to assess the extent and depth of tsunami inundation. In the analysis of tourism suitability based on tsunami disaster mitigation, the suitable tourism area is located in the eastern part of Sidoarjo Village and the entire Ploso Village. These areas fall into the high tsunami risk zone, but their tourism potential is also high due to the coastal location of tourist attractions